2010
DOI: 10.1080/10934529.2010.520510
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of polyether algal toxins–Isolation of potential marine bacteria

Abstract: Marine algal toxins such as brevetoxins, okadaic acid, yessotoxin, and ciguatoxin are polyether compounds. The fate of polyether toxins in the aqueous phase, particularly bacterial biotransformation of the toxins, is poorly understood. An inexpensive and easily available polyether structural analog salinomycin was used for enrichment and isolation of potential polyether toxin degrading aquatic marine bacteria from Florida bay area, and from red tide endemic sites in the South Florida Gulf coast. Bacterial grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Indeed, bacteria are known to preferentially target oxygen-rich molecules over several days [53,54], explaining their affinity for highly hydroxylated molecules like OVTX and LGTX [5,8] as confirmed by the untargeted approach. These transformation rates are comparable with those of saxitoxin and neosaxitoxin obtained after 12 to 24 h (>90%, [29]), but were much quicker than those obtained for gonyautoxin [29], PbTx-2 [30] or microcystin-LR [31]. Other studies on PbTx-2 suggest a rapid (<24 h) microbial breakdown that is mediated by microalgae and not bacteria [55,56].…”
Section: Rapid Transformation Of Ovtx and Lgtx By Bacteriasupporting
confidence: 75%
See 2 more Smart Citations
“…Indeed, bacteria are known to preferentially target oxygen-rich molecules over several days [53,54], explaining their affinity for highly hydroxylated molecules like OVTX and LGTX [5,8] as confirmed by the untargeted approach. These transformation rates are comparable with those of saxitoxin and neosaxitoxin obtained after 12 to 24 h (>90%, [29]), but were much quicker than those obtained for gonyautoxin [29], PbTx-2 [30] or microcystin-LR [31]. Other studies on PbTx-2 suggest a rapid (<24 h) microbial breakdown that is mediated by microalgae and not bacteria [55,56].…”
Section: Rapid Transformation Of Ovtx and Lgtx By Bacteriasupporting
confidence: 75%
“…The extraction efficiency achieved with the two other polymeric sorbents HLB and StrataX was not significantly lower than for the SDBL sorbent; however, these two phases did not provide good reproducibility and had a longer processing time. Despite similar functional groups, the StrataX and the HLB sorbents did not display the same behavior; this difference might be attributed to the differences in their particle sizes (28)(29)(30)(31)(32)(33)(34) µm in StrataX against 50-65 µm in HLB).…”
Section: Sdbl Cartridges Offer the Best Compromise For The Extraction...mentioning
confidence: 93%
See 1 more Smart Citation
“…The differences seen between the toxins in cells compared to the resin may reflect a contrast between what is excreted by cells and what is retained intracellularly as Nagai et al [ 54 ] demonstrated the release of extracellular toxins in cultures of Dinophysis acuminata. Alternatively, differences could also reflect the transformation of these toxins within the water column via bacterial degradation (as seen for other toxins; [ 55 , 56 ]). While this study found that SPATT samplers were able to detect toxins in the water column 3–4 weeks earlier than shellfish detections and MacKenzie et al [ 22 ] reported SPATT DSP detection at least a week earlier than shellfish, Pizarro et al [ 28 ] found that Dinophysis cells provided a more reliable early warning of shellfish toxicity than SPATT.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of knowledge on the fate of brevetoxins in marine waters after a bloom has subsided and K. brevis cell counts return to baseline levels. Known sinks of brevetoxins in marine water columns are biological uptake and metabolism (Redshaw et al, 2010;Shetty et al, 2010;Bricelj et al, 2012), export via aerosols (Pierce et al, 2003) sorption to sediments (Pierce et al, 2004;Hitchcock et al, 2012;Mendoza et al, 2008), and photodegradation (Kieber et al, 2010). Mendoza et al (2008) reported detectable levels of brevetoxins in surface sediments collected five months after a K. brevis bloom.…”
Section: Introductionmentioning
confidence: 99%